The Impact of Digital Innovation on the Financial Stability of Commercial Banks: A Comparative Study in Nascent Markets - حسين رائد قائد; شاكر فاطمة جواد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study examines the impact of digital innovation on the financial stability of commercial banks in emerging markets, with a particular focus on the Middle East and North Africa (MENA) region. The topic is important given the rapid transformations taking place in the global banking sector due to digitalization, and the opportunities it presents for enhancing efficiency and financial inclusion, while simultaneously posing potential risks related to cyberattacks, financial interconnectedness, and weak infrastructure and governance. The study adopted a quantitative approach using panel data for a number of emerging countries over the period (2011–2023), drawing on Global Findex and IMF Financial Access Survey databases, as well as specialized international reports. Digital innovation was measured through indicators such as digital payments, e-wallets, and the number of active bank cards, while financial stability was measured through indicators such as the Z-score, non-performing loan ratio (NPL), and capital adequacy ratio (CAR). The study used a fixed effects (FE) model to test the relationship, in addition to a System GMM model to address reverse causality. - The results showed that digital innovation is positively associated with financial stability at moderate levels of use, but its effect shifts to negative when relied upon excessively, confirming the existence of an inverted U relationship. The results also showed that the impact varied across regions. It was strong in the Gulf countries and emerging Asia, thanks to infrastructure, while it was weak or negative in some North African and Sub-Saharan African countries due to weak oversight and operational risks. - The study provided policy recommendations for central banks and decision-makers regarding the need to strengthen regulatory and supervisory frameworks, develop cybersecurity policies, support digital financial inclusion, and promote international cooperation in the field of financial technology. It also recommended that commercial banks invest in digital infrastructure and develop early warning systems for risks, while calling on customers and investors to increase digital financial awareness.